The Effect of Grinding and Polishing on Roughness of Zirconia and its Consequent Effect on Mechanical Behavior. - Khayat, Waad. (2017)
Abstract: Aim and Hypothesis: The aim of the study was to compare roughness average (Ra) of aged zirconia specimens that received different surface treatment of grinding and polishing and to investigate whether roughness has an influence on the mechanical properties of ground and polished zirconia. Hypothesis stated that grinding and polishing would significantly increase roughness average and significantly decrease biaxial flexural strength among treatment groups in comparison to glazed control group. Materials and method: A total of 44 high translucent zirconia discs (ø 15 = mm, thickness = 1.5 mm) were milled, sintered, ultrasonically cleaned and glazed according to the manufacturers' recommendations. Specimens were equally randomized into four groups. The first group (A) received grinding only. The second and third groups (B and C) received grinding and polishing with two different polishing systems. The fourth group (D) was the glazed control group and did not receive any grinding or polishing. All specimens were subjected to hydrothermal aging using an autoclave at 134° C and 2 bars for 3 hours. Roughness average was measured in μm using 3-D optical interferometer at baseline (Ra 1), after grinding and polishing as designed for each group (Ra 2) and after aging (Ra 3). Biaxial flexural strength test was performed at a rate of 0.5 mm/min until failure occurred and biaxial flexural strength was calculated in MPa. Results: The study found that group (A) showed a significantly higher mean value of Ra 3 (1.96 ±0.32) in comparison to polished and glazed groups (B, C and D), which showed no statistically significant difference between them (1.12 ± 0.31, 0.88 ± 0.31, 0.87 ± 0.25 respectively). Compared to baseline, roughness of groups A and B was significantly increased after grinding and polishing as well as after aging, while roughness of groups C and D was not further significantly influenced by aging. Group A showed the lowest mean value of biaxial flexural strength (879.01 ±157.99) and the highest value was achieved by group C (962.40 ± 113.84), but there was no statistically significant difference among groups (p > 0.05). Also, no significant correlation was detected between roughness average and biaxial flexural strength of zirconia (p > 0.05). Conclusion: Grinding increases roughness of zirconia restorations while proper polishing can result in smoothness comparable to glazed untreated surface. Rough zirconia restorations are more prone to the negative influence of aging than smooth ones. Also, grinding and polishing has no significant effect on flexural strength of zirconia. Furthermore, the deterioration of the mechanical properties of zirconia is not a result of roughness.; Thesis (M.S.)--Tufts University, 2015.; Submitted to the Dept. of Other.; Advisor: Najla Chebib.; Committee: Ala Ali, Matthew Finkelman, and Samer Khayat.; Keyword: Dentistry.